2006
DOI: 10.1038/nmeth999
|View full text |Cite
|
Sign up to set email alerts
|

Retrograde neuronal tracing with a deletion-mutant rabies virus

Abstract: We have constructed a deletion-mutant rabies virus encoding EGFP and find it to be an excellent tool for studying detailed morphology and physiology of neurons projecting to injection sites within the mammalian brain. The virus cannot spread beyond initially infected cells yet, unlike other viral vectors, replicates its core within them. The cells therefore fluoresce intensely, revealing fine dendritic and axonal structure with no background from partially or faintly labeled cells.A fundamental question regard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
686
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 623 publications
(700 citation statements)
references
References 10 publications
14
686
0
Order By: Relevance
“…As the experiments reported in our study affected LRP4 expression only in neurons (due to the neuron-specific synapsin promoter), the altered spine density that we observed must be caused by changes in neuronally expressed LRP4. Moreover, using a rabies virus-mediated monosynaptic tracing technique (Wickersham et al, 2007a), we demonstrated that the decreased number of synapse-like specializations and dendritic spines mediated by the expression of LRP4 miRNAs is paralleled by a decrease in the number of synaptic inputs as well, and therefore functional synapses. Hippocampal and cortical neurons in culture also responded to reduced LRP4 expression by changes in dendritic morphology.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…As the experiments reported in our study affected LRP4 expression only in neurons (due to the neuron-specific synapsin promoter), the altered spine density that we observed must be caused by changes in neuronally expressed LRP4. Moreover, using a rabies virus-mediated monosynaptic tracing technique (Wickersham et al, 2007a), we demonstrated that the decreased number of synapse-like specializations and dendritic spines mediated by the expression of LRP4 miRNAs is paralleled by a decrease in the number of synaptic inputs as well, and therefore functional synapses. Hippocampal and cortical neurons in culture also responded to reduced LRP4 expression by changes in dendritic morphology.…”
Section: Discussionmentioning
confidence: 92%
“…Furthermore, changes in frequency of mEPSCs are not always proportional to the number of synapses, as changes in the stochastic release of presynaptic neurotransmitters or density of postsynaptic receptors could affect the mEPSC values as well. Thus, to further examine whether LRP4 expression levels affect synaptic connectivity, we used the rabies virus-mediated monosynaptic tracing technique, a method that allows an efficient analysis of functional presynaptic partners (Wickersham et al, 2007a). For that, cortical neurons were transfected with a retroviral vector encoding the EnvA-receptor TVA, the rabies virus glycoprotein G (which is responsible for retrograde transport of the virus across synapses), and the fluorescent reporter DsRedExpress2 (Fig.…”
Section: Knockdown Of Lrp4 Reduces the Number Of Direct Presynaptic Pmentioning
confidence: 99%
See 2 more Smart Citations
“…Now, several serotypes of adeno-associated virus (AAV) such as AAV6, AAV8, and AAV9 are characterized to transduce neurons retrogradely [61][62][63][64][65], and lentivirus has been modified with its glycoprotein fused with rabies virus glycoprotein for retrograde transduction [41,42,66,67]. These viruses are easy to produce, result in less inflammation than herpes simplex and rabiesderived vectors, and have long duration and high level of transgene expression [68][69][70][71][72].…”
Section: Spatial Controlmentioning
confidence: 99%